Navigating family planning access during Covid-19: A qualitative study of young women's access to information, support and health services in peri-urban Nairobi - Rahma Hassan; Amiya Bhatia; Anja Zinke-Allmang; Amy Shipow; Concilia Ogolla; Krittika Gorur; Beniamino Cislaghi (Elsevier, 2022)
The COVID-19 response has profoundly affected women's access to family planning services in Kenya. While prior studies have shown how the COVID-19 response created barriers to accessing family planning (FP) services, less is known about how the pandemic affected the normative influence that partners, peers, and health providers exert on women's FP choices. In this qualitative study, we interviewed 16 women (aged 18-25 years), 10 men in partnerships with women, and 14 people in women's social networks across 7 low-income wards in Nairobi, Kenya. Our findings suggest that COVID-19 response measures changed the contexts of normative influence on FP: financial insecurity, increased time at home with husbands or parents, and limited access to seek the support of health workers, friends, and other people in their social network affected how women negotiated FP access and use within their homes. Our study underscores the importance of ensuring FP is an essential service in a pandemic, and of developing health programs that change norms about FP to address the gendered burden of negotiating FP during COVID-19 and beyond.